Segmental epidural anaesthesia for percutaneus kyphoplasty - Apan, Alparslan; Cuvaş Apan, Özgün; Köse, Emine Arzu (Lippincott Williams & Wilkins, 2014)
[Abstract Not Available]
European Anaesthesiology Congress (Euroanaesthesia) -- MAY 31-JUN 03, 2014 -- Stockholm, SWEDEN
WOS: 000209832000370
Keywords: Segmental Epidural Anaesthesia; Percutaneus Kyphoplasty